The prevalence of thromboembolic events among COVID-19 patients admitted to a single centre intensive care unit (ICU): an epidemiological study from a Malaysian population - Nur Farhani Mansor; Izzati Abdul Halim Zaki; Lee Chew Kiok; Eng Kar Seng; Tharmini Ravi; Mohan Pathmanathan; Khang Wen Goh; Long Chiau Ming; Pakhrur Razi; Hanis Hanum Zulkifly (Journal of Pharmaceutical Policy and Practice)
Introduction Thromboembolic (TE) complications in COVID-19 patients are rising globally, contributing significantly to mortality, particularly in severe cases. However, their prevalence, characteristics, and impact on mortality in Malaysia remain unclear.Objectives This study aimed to determine the prevalence of thromboembolic (TE) events and associated mortality among COVID-19 patients admitted within a single centre intensive care unit (ICU). The proportions of patients with TE events who died, and factors associated with TE events were explored.Methods In this retrospective cohort study, patients with PCR confirmed SARS-CoV-2 virus and who received thromboprophylaxis within February 2020–2021 were included. TE event is a combination of venous [(deep vein thrombosis (DVT), pulmonary embolism (PE)] and arterial (myocardial infarction (MI), stroke) thromboembolism.Results Mean (SD) age 56.6 (13.7), 63.5% were male, 61.6% Malays, median (IQR) 7 (3–14) days of ICU stay, 64.2%, 53.2% and 20.9% had underlying hypertension, diabetes and obesity respectively. In total, 240 (44.9%) developed TE event. Significantly higher proportions of COVID-19 patients who developed complications of DVT (2.5% vs. 0.2%; p = 0.013), PE (47.5% vs 34.0%; p = 0.006), stroke (12.3% vs. 1.5; p<0.001) and MI (16.4% vs. 4.6%; p<0.001) died. Predictors of TE events were age [HR 1.01 (95% CI 1.00–1.02)], obesity [HR 1.98 (95% CI 1.51–2.6)], D-dimer [HR 1.01 (95% CI 1.00–1.01)], and duration of ICU stay [HR 0.98 (95% CI 0.97–0.99)].Conclusion In severely ill COVID-19 patients, TE complications were common, and patients with DVT, PE, stroke, or MI faced increased mortality, even with thromboprophylaxis. Age, obesity, elevated D-Dimer levels, and longer ICU stays were significant predictors of TE events. Considering these findings, a more aggressive approach, combining thromboprophylaxis with enhanced anti-inflammatory treatments, may be necessary for high-risk COVID-19 ICU patients to reduce TE events and mortality.